Microstructural insight on strain-induced crystallization of ethylene/propylene(/diene) random copolymers. (16th June 2021) - Auriemma, Finizia; Scoti, Miriam; De Stefano, Fabio; Talarico, Giovanni; Ruiz de Ballesteros, Odda; Di Girolamo, Rocco; Malafronte, Anna; De Rosa, Claudio; Cipullo, Roberta; Van Duin, Martin
Abstract: The tensile properties and the structural transformations occurring by effect of deformation of un-vulcanized ethylene/propylene(/diene) elastomers with ethylene contents ranging from 57 to 83 mol% are analyzed and interpreted in terms of the chain microstructure. It is shown that the samples with ethylene contents larger than or equal to 73 mol% experience a slight but significant increase of crystallinity upon stretching and partial melting of the new oriented crystals formed by stretching after releasing the tension. The degree of crystallinity, the tensile properties, the incremental crystallinity achieved upon stretching and the residual crystallinity left upon release of the tension all show well-defined correlations with the average ethylene content and the ethylene sequence length distribution. The tensile properties and the strain hardening behavior are correlated with the incremental crystallinity achieved upon stretching at high strain. Graphical abstract: Image 1 Highlights: The structure & properties of ethylene/propylene(/diene) rubbers are investigated. The chain microstructure controls the strain induced crystallization (SIC). For ethylene content >80 mol%: moderate SIC entails moderate strain hardening (SH). For ethylene content <80 mol% and >70 mol%: high SIC entails high SH. For ethylene content <70 mol%: low SIC entails low SH.